D1244: Design and Construction of the First Adaptive High-Rise Experimental Building - Blandini, Lucio; Haase, Walter; Weidner, Stefanie; Böhm, Michael; Burghardt, Timon; Roth, Daniel; Sawodny, Oliver; Sobek, Werner (Frontiers in Built Environment, 2022)
An interdisciplinary research team of the University of Stuttgart has been working extensively since 2017 on the development and integration of adaptive systems and technologies in order to provide solutions for a more sustainable built environment. An experimental 36.5 m tall high-rise building, called D1244, was designed and completed in 2021 to show the potential of adaptive structures and facades as well as to verify on a real scale the developed systems and the related numerical predictions. The building was designed to offer a flexible experimental platform: each component is dismountable so that structural as well as facades elements can be replaced with new ones introducing new functionalities to be investigated. The structure is currently equipped with twenty-four hydraulic actuators that are installed in the columns and diagonal bracers. Strain gauge sensors and an optical tracking system are employed to monitor the state of the structural system. This paper describes the design and construction of the adaptive tower as well as the preliminary experimental testing on different scaled structural prototypes. The research work on these prototypes provided relevant information for the final set-up of the high-rise building. An outlook on future research, including the planned first structural testing phase and the implementation of adaptive façade systems, is included at the end.